Finding the Strategy After Corona Crisis: The New Normal and Resilient Economy Growth in Indonesia - Hidayatullah, Dicky Ramadhan; Darmawan, Arif; Kallidumban, Shamsad (FEB - Universitas Lampung, 2020)
The research method used to analyze the situation and conditions in making this paper is a qualitative method. As an analysis procedure, qualitative methods can produce descriptive data in the form of written or spoken words from people or observable behavior. This pandemic comes with all its negative effects. Inequality, poverty, and education are the most affected lines in this pandemic because they reduce the income of vulnerable and poor groups. Many parties assess the world economy is far worse than before the corona. Weakening global economic growth caused many impacts on the pace of economy in Indonesia, both in terms of trade, investment and tourism. Thus, changing the projected economic growth becomes even slower due to the spread of Covid-19 throughout the country. Although we know that the Indonesian government has issued a policy of hundreds of trillions of rupiah to save our economy, social impact, poverty, and Equality. The Indonesian government has currently budgeted funds of Rp405.1 Trillion for handling Covid-19. The budget allocation will be divided for several sectors, such as the health sector in the amount of Rp75 Trillion, Social Safety Net of Rp110 trillion, tax incentives and stimulus for People's Business Credit (KUR) of Rp70.1 trillion, and funding for the national economic recovery program of Rp150 Trillion, including credit restructuring and guarantees